2012
DOI: 10.1016/j.virusres.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Typing of canine parvovirus strains circulating in Brazil between 2008 and 2010

Abstract: Detection and characterisation of the canine parvovirus (CPV-2) strains that are currently circulating are essential for the understanding of viral evolution and the development of measures to control its spread. In the present study, stool samples from 144 dogs were analysed by polymerase chain reaction (PCR) for CPV-2, and 29.2% (42/144) of them were positive. From the 42 positive strains, 71.4% (30) of the dogs had signs of haemorrhagic gastroenteritis. The sequencing of the 583 bp fragment of the VP2 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 22 publications
7
40
2
1
Order By: Relevance
“…In accordance with Pinto et al (2012), the amino acid substitution Thr440Ala was not observed in any CPV-2c sequences, as previously described in CPV-2a and CPV-2b strains from Italy (Battilani et al 2002), India (Chinchkar et al 2006), Korea (Kang et al 2008), and in CPV-2c strains from Argentina (Calderón et al 2011) and Italy (Decaro et al 2009). The 440 position is located at an important VP2 domain, undergoing positive selection and envolved independently in different populations ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with Pinto et al (2012), the amino acid substitution Thr440Ala was not observed in any CPV-2c sequences, as previously described in CPV-2a and CPV-2b strains from Italy (Battilani et al 2002), India (Chinchkar et al 2006), Korea (Kang et al 2008), and in CPV-2c strains from Argentina (Calderón et al 2011) and Italy (Decaro et al 2009). The 440 position is located at an important VP2 domain, undergoing positive selection and envolved independently in different populations ).…”
Section: Discussionsupporting
confidence: 87%
“…Pinto et al (2012) demonstrated that CPV-2c has been the main subtype detected in the canine population of some regions of Brazil, as previously found in the Uruguay (Pérez et al 2007), Italy ), Germany (Decaro et al 2011a), and Argentina (Calderón et al 2011). Therefore, it is important to identify emerging CPV variants and developing preventive measures to control the spread of CPV-2 variants.…”
Section: Introductionmentioning
confidence: 52%
“…In our study, only one dog was infected with the genotype CPV-2a and another one with CPV-2c. Pinto et al (2010), a group of researchers from Rio Grande do Sul, Brazil, studied samples from six different Brazilian states and found CPV-2c to be the predominant subtype. The predominance of CPV-2c was reported by Calderón et al (2011) in Argentina, and the close proximity of Argentina to the Rio Grande do Sul suggests that regional viral circulation could be responsible for the detection of the same subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that there was no interference in the ability of commercial vaccines to protect puppies against circulating canine parvovirus, but they did suggest the need to continue monitoring for new variants. Pinto et al (2010) reported that for 42 canine parvovirus-positive samples, 78.6% (33/42) of the samples were type 2c, 19% (8/42) were type 2b, and 2.4% (1/42) were type 2a.…”
Section: Introductionmentioning
confidence: 99%
“…During the last ten years, a novel CPV mutant, CPV-2c, has widely distributed and co-exists with other CPV types in Europe , North (Hong et al 2007) and South (Perez et al 2007) America countries. The identification of the subtypes of CPV-2 that are currently circulating in the canine population is essential for the understanding of viral evolution and the development of measures to control its spread (Pinto et al 2012). All the three antigenic variants differ from the original type CPV-2 for a few amino acids in the VP2 protein, whereas genetic differences among the variants are determined only by residue 426, with types 2a, 2b, and 2c displaying Asn, Asp, and Glu, respectively (Martella et al 2006).…”
Section: Introductionmentioning
confidence: 99%